A new class of valid inequalities for the round robin tournament problem - Andrei Horbach (Universität Kiel, Institut für Betriebswirtschaftslehre, 2008)
We introduce a new class of valid inequalities for the maximum round robin tournament (MRRT) problem. They strengthen the linear relaxation and improve the upper bound. We also answer negatively the question of Briskorn if the optimal objective value of the MRRT problem and that of its conventional linear relaxation always coincide.
Keywords: 650; round robin tournaments; valid inequalities; linear relaxation; Sport; Scheduling-Verfahren; Theorie